Konsep Pendidikan Kebebasan dalam Pembelajaran Bahasa Jerman Kurikulum Merdeka Menggunakan Analisis Paulo Freire - Aulia, Ajma; Dalle, Ambo; Al Ilmullah3, Syarifah Fathimah (Academic : Journal of Social and Educational Studies, 2025)
Abstract. Falling This study is a descriptive qualitative research that aims to examine the application of the concept of freedom and its impact in learning German in the Merdeka Curriculum at SMAN 4 Enrekang, using Paulo Freire's perspective. This research focuses on the dialectical process and interaction between teachers and students during German language learning. Data were obtained through observations, recordings of the learning process, and related documents, then analyzed using Paulo Freire's freedom analysis method. The results showed that three main aspects were successfully implemented, namely dialog, cultural and contextual context, and empowerment. However, the involvement of praxis is still not maximized, and the other two aspects of criticism of traditional education and education as a political act are still not well implemented. The positive impact of applying Paulo Freire's concept of freedom is seen in students' ability to think critically, which increases their engagement, as well as the social context that encourages students to continue learning German. However, some students still have difficulty responding because they are used to authoritarian learning methods.Keywords: German, Freedom, Paulo Freire